1990
DOI: 10.1021/ma00221a004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unidirectional shear on the structure of triblock copolymers. 2. Polystyrene-polyisoprene-polystyrene

Abstract: Rheological and small-angle X-ray scattering (SAXS) measurements on a polystyrenepolyisoprene-polystyrene block copolymer indicate that high-strain, high-stress unidirectional shear flow in the microphase-separated regime produces a well-oriented, microdomain structure with cylindrical microdomains. Experiments in low-stress, high-strain flow produced little orientation. The material studied is a high molecular weight copolymer with 24 vol % polystyrene and a cylindrical microdomain morphology as indicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 4 publications
1
57
0
Order By: Relevance
“…Much less attention has been given to the rheological behaviour of triblock copolymers in the lamellar phase. [13][14][15] Studies so far have focused on cylindrical domains [16][17][18][19][20][21][22][23][24] and on triblock copolymer solutions. [25] The main emphasis of our present work is to compare the orientation behaviour and the kinetics between phase separated linear diblock and linear triblock copolymer under LAOS conditions.…”
Section: Full Papermentioning
confidence: 99%
“…Much less attention has been given to the rheological behaviour of triblock copolymers in the lamellar phase. [13][14][15] Studies so far have focused on cylindrical domains [16][17][18][19][20][21][22][23][24] and on triblock copolymer solutions. [25] The main emphasis of our present work is to compare the orientation behaviour and the kinetics between phase separated linear diblock and linear triblock copolymer under LAOS conditions.…”
Section: Full Papermentioning
confidence: 99%
“…27 As noted earlier, zero measured birefringence in the 1-3 plane is consistent with parallel alignment, but confirms neither it nor provides a measure of the quality of the orientation state. Using the oblique light path methods described in section 2.3.3, it is possible to characterize the degree of alignment achieved by oscil- a T ) (6.14 × 10 -12 )e 7672/T(K) (7) latory flow at high frequencies. The specialized flow cells for these measurements are, however, limited to room-temperature experiments.…”
Section: Alignment In Oscillatory Shear Flowmentioning
confidence: 99%
“…In this case, the effective composition f", associated with the statistical segments of blocks measured along the field is equal: j~"'p N. I -f Keller, Pedemonte, and Willmouth [11], Hadziioannou et al [12), Balsara and Hammouda [13], Rorno-Uribe and Windle [14], and Albalak and Thomas [15] studied the alignment of hexagonally cylindrical and lamellar microdomains in diblock copolymers, solvated diblock copolymers, and random copolymers, respectively, under deformations. Le Meur et al [16]reported on a shift of the order-disorder transition temperature by a shear, and Morrison et al [17] have shown that the degree of phase mixing depends on the strain. Finally, reorientational transitions in dynamically sheared diblock copolymers were recently observed by Koppi et al [18].…”
Section: Reentrant Phase Transitionsmentioning
confidence: 99%